2021
DOI: 10.1177/00037028211055213
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization Using Laser-Induced Breakdown Spectroscopy of Products Released from Lithium-Ion Battery Cells at Thermal Runaway Conditions

Abstract: Laser-induced breakdown spectroscopy (LIBS) was used to characterize the materials released by lithium-ion (Li-ion) cells at thermal runaway conditions. Commercial AAA-size, rechargeable, 3.7-V, 350-mAh, Li-ion battery cells were heated in a N2-atmosphere tubular chamber up to about 165 °C to induce thermal decomposition. Through measurements of the chamber internal temperature and LIBS emission intensities over time the onset temperature of thermal runaway (≈143 °C) and the duration of the cells outgassin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Although such intensity variations are common in LIBS sampling of other substances (see for example the analysis of solids 48 ), they are intensified while analyzing aerosols due to the inherent discrete nature of aerosol streams and LIBS sampling characteristics. Such intensity variations have been previously reported during the analysis of aerosol streams under laboratory 44,46,47 and industrial conditions. 43 Third, the ensemble-averaged spectrum of multiple single-shot spectra was flat or featureless at the analyte wavelengths, indicating that discrete sampling of aerosol particles occurred.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although such intensity variations are common in LIBS sampling of other substances (see for example the analysis of solids 48 ), they are intensified while analyzing aerosols due to the inherent discrete nature of aerosol streams and LIBS sampling characteristics. Such intensity variations have been previously reported during the analysis of aerosol streams under laboratory 44,46,47 and industrial conditions. 43 Third, the ensemble-averaged spectrum of multiple single-shot spectra was flat or featureless at the analyte wavelengths, indicating that discrete sampling of aerosol particles occurred.…”
Section: Discussionsupporting
confidence: 77%
“…4-6 are representative of LIBS aerosol sampling. 12,[43][44][45][46][47] First, only a small portion of the total single-shot spectra displayed the analyte emission lines. Second, the intensity of the particle hits (i.e., the occurrence of analyte-plasma interaction and signal detection) varied considerably from low to high intensities.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear, however, that studies of the temperature dependence of the LIBS signal of volatile species in molten metals can provide valuable information about their behavior in the melt, for example, the effects of microalloying for the mitigation of oxidative loss of Mg. 25 In a recent study, LIBS measurements on off-gassed Na and Ca from molten salts were reported, where the analysis was performed in a chamber that was separated from the molten salt reactor. 26 Such studies, as well as experimental configurations where a breakdown is localized in the vapor phase above a liquid surface, will be of value to further elucidate the mechanisms of evaporation, without contributions from the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…Diaz and Hahn used LIBS to characterise products released from lithium ion battery cells at thermal runaway conditions . 232 Commercial AAA-sized 3.7 V, 350 mA h lithium ion batteries were placed in a heating chamber and heated to 165 °C to induce thermal decomposition (this starts at 143 °C) in a nitrogen atmosphere. Any gases emitted over a 40 minute period were then analysed on-line using LIBS which employed a Nd:YAG laser, optics, a chamber in which the LIBS analysis occurred and a spectrometer equipped with an intensified CCD.…”
Section: Inorganic Materialsmentioning
confidence: 99%